0.4(3x-0.1)=0.5x+2

Simple and best practice solution for 0.4(3x-0.1)=0.5x+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.4(3x-0.1)=0.5x+2 equation:



0.4(3x-0.1)=0.5x+2
We move all terms to the left:
0.4(3x-0.1)-(0.5x+2)=0
We multiply parentheses
1.2x-(0.5x+2)-0.04=0
We get rid of parentheses
1.2x-0.5x-2-0.04=0
We add all the numbers together, and all the variables
0.7x-2.04=0
We move all terms containing x to the left, all other terms to the right
0.7x=2.04
x=2.04/0.7
x=2+0.64/0.7

See similar equations:

| 9-2x=3x-11 | | 5x+11=2x-11 | | 39-5x=2x+17 | | 1/3x^2-2x+3=0 | | 4(2l*2)=40 | | 4(2l2)=40 | | (3x-7)=-15+35 | | (3-7)=-15x | | (3x-7)=15x+35 | | (k+77)2=289 | | Y=4x+3/2x-1 | | (0.16÷r)-1=3÷5 | | 2/7-1/3x=1/2 | | 9x+68=x | | 60t=24(6+t) | | (5x-3)^2=32 | | (5x-3)^2=-32 | | 3/5a+1/2a=11 | | 25/40=14/x | | 4(y-5)=2(3-2y) | | (5/v+5/v+10)=4/3 | | (r+2)^2=25 | | 5/v+5/v+10=4/3 | | 2x^-17x-1=0 | | 5+6(x+1)=41 | | 9(x^2-2x+1)=0 | | 9x+1=6(x=1) | | 24x+2=4x+242 | | .75(x+12)+7=2(x-3)+12 | | 8x+18=-4 | | 3(4y+9)=7(2-5y)=2y | | 4a-7/6-2/3+3/2=0 |

Equations solver categories